2023
DOI: 10.5194/tc-17-2965-2023
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning subgrid-scale parametrisations for short-term forecasting of sea-ice dynamics with a Maxwell elasto-brittle rheology

Abstract: Abstract. We introduce a proof of concept to parametrise the unresolved subgrid scale of sea-ice dynamics with deep learning techniques. Instead of parametrising single processes, a single neural network is trained to correct all model variables at the same time. This data-driven approach is applied to a regional sea-ice model that accounts exclusively for dynamical processes with a Maxwell elasto-brittle rheology. Driven by an external wind forcing in a 40 km×200 km domain, the model generates examples of sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…ML models have been shown to be successful at parameterizing subgrid‐scale processes within dynamical models, including ocean mesoscale eddies (Guillaumin & Zanna, 2021), atmospheric convection (Yuval & O’Gorman, 2020), and sea ice dynamics (Finn et al., 2023). Common to each of these studies is that the ML models target specific physical processes, with the aim of replacing pre‐existing knowledge‐based parameterizations, or deriving new parameterizations for physical processes which are not currently represented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML models have been shown to be successful at parameterizing subgrid‐scale processes within dynamical models, including ocean mesoscale eddies (Guillaumin & Zanna, 2021), atmospheric convection (Yuval & O’Gorman, 2020), and sea ice dynamics (Finn et al., 2023). Common to each of these studies is that the ML models target specific physical processes, with the aim of replacing pre‐existing knowledge‐based parameterizations, or deriving new parameterizations for physical processes which are not currently represented.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of dynamical climate models, DL algorithms have proven effective tools for deriving model parameterizations directly from numerical simulations. For example, many past studies have focused on learning subgrid parameterizations from high resolution experiments and/or observations of the ocean (Bolton & Zanna, 2019; Sane et al., 2023; Zanna & Bolton, 2020; Zhu et al., 2022), atmosphere (Brenowitz & Bretherton, 2018; Gentine et al., 2018; O’Gorman & Dwyer, 2018; Rasp et al., 2018; P. Wang et al., 2022; Yuval & O’Gorman, 2020), and sea ice (Finn et al., 2023). In the context of DA‐based approaches, some recent studies have relied on iterative sequences of DA and ML to infer unresolved scale parameterizations from sparse and noisy observations (Brajard et al., 2021), or to learn state‐dependent model error from analysis increments (Farchi et al., 2021) and nudging tendencies (Bretherton et al., 2022; Watt‐Meyer et al., 2021), while others have combined DA with equation discovery to extract interpretable structural model errors (Mojgani et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, only recently have studies begun to investigate ML-based subgrid sea ice parameterizations. For example, Finn et al (2023) successfully demonstrated an ML-based sea ice parameterization which learns short timescale errors associated with subgrid sea ice dynamics in a low resolution sea ice model. Furthermore, Driscoll et al (2023) showed success in emulating a sea ice melt pond parameterization using neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Finn et al. (2023) successfully demonstrated an ML‐based sea ice parameterization which learns short timescale errors associated with subgrid sea ice dynamics in a low resolution sea ice model. Furthermore, Driscoll et al.…”
Section: Introductionmentioning
confidence: 99%
“…Even though hybrid models can be more difficult to implement than surrogate models, they are often more accurate while reducing data demands (Watson, 2019;Farchi et al, 2021b). There are many examples of hybrid modelling in the geosciences, ranging from data-driven subgrid scale parametrisations (Rasp et al, 2018;Bolton and Zanna, 2019;Gagne et al, 2020;Finn et al, 2023;Ross et al, 2023) to generic model error correction (Bonavita and Laloyaux, 2020;Wikner et al, 2020;Farchi et al, 2021b,a;Brajard et al, 2021;Chen et al, 2022) and super resolution (Barthélémy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%